Hog1 Regulates Stress Tolerance and Virulence in the Emerging Fungal Pathogen Candida auris - Alison M. Day (American Society for Microbiology, 2018)
ABSTRACT Candida auris has recently emerged as an important, multidrug-resistant fungal pathogen of humans. Comparative studies indicate that despite high levels of genetic divergence, C. auris is as virulent as the most pathogenic member of the genus, Candida albicans. However, key virulence attributes of C. albicans, such as morphogenetic switching, are not utilized by C. auris, indicating that this emerging pathogen employs alternative strategies to infect and colonize the host. An important trait required for the pathogenicity of many fungal pathogens is the ability to adapt to host-imposed stresses encountered during infection. Here, we investigated the relative resistance of C. auris and other pathogenic Candida species to physiologically relevant stresses and explored the role of the evolutionarily conserved Hog1 stress-activated protein kinase (SAPK) in promoting stress resistance and virulence. In comparison to C. albicans, C. auris is relatively resistant to hydrogen peroxide, cationic stress, and cell-wall-damaging agents. However, in contrast to other Candida species examined, C. auris was unable to grow in an anaerobic environment and was acutely sensitive to organic oxidative-stress-inducing agents. An analysis of C. auris hog1Δ cells revealed multiple roles for this SAPK in stress resistance, cell morphology, aggregation, and virulence. These data demonstrate that C. auris has a unique stress resistance profile compared to those of other pathogenic Candida species and that the Hog1 SAPK has pleiotropic roles that promote the virulence of this emerging pathogen. IMPORTANCE The rapid global emergence and resistance of Candida auris to current antifungal drugs highlight the importance of understanding the virulence traits exploited by this human fungal pathogen to cause disease. Here, we characterize the stress resistance profile of C. auris and the role of the Hog1 stress-activated protein kinase (SAPK) in stress resistance and virulence. Our findings that C. auris is acutely sensitive to certain stresses may facilitate control measures to prevent persistent colonization in hospital settings. Furthermore, our observation that the Hog1 SAPK promotes C. auris virulence akin to that reported for many other pathogenic fungi indicates that antifungals targeting Hog1 signaling would be broad acting and effective, even on emerging drug-resistant pathogens.